2010
DOI: 10.1097/brs.0b013e3181ba1359
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Mortality After Traumatic Spinal Cord Injury

Abstract: STUDY DESIGN.: Retrospective cohort study. OBJECTIVE.: To identify predictors of early mortality following traumatic spinal cord injury (TSCI). SUMMARY OF BACKGROUND DATA.: Limited information is available on factors associated with early mortality following TSCI. Ability to identify high risk individuals can help to appropriately treat them, and reduce mortality. METHODS.: Early mortality was defined as death occurring during the initial hospital admission. Retrospective analysis of 1995 patients with TSCI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 31 publications
4
96
0
2
Order By: Relevance
“…11 Studies also accounted for polytrauma using the count of injuries in various body regions. 3, 6 We did not find any published study that evaluated TSCI mortality in large population with counts of comorbid conditions, injuries and their joint effects. The purpose of this study was to identify mutable risk factors of in-hospital death among TSCI patients accounted by the counts of comorbidities, injuries and their joint effects using timeto-event analyses.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…11 Studies also accounted for polytrauma using the count of injuries in various body regions. 3, 6 We did not find any published study that evaluated TSCI mortality in large population with counts of comorbid conditions, injuries and their joint effects. The purpose of this study was to identify mutable risk factors of in-hospital death among TSCI patients accounted by the counts of comorbidities, injuries and their joint effects using timeto-event analyses.…”
Section: Introductionmentioning
confidence: 78%
“…As noted in other studies, 4 having a single comorbidity did not show a significant effect on mortality. Overall, studies that used counts showed better risk estimates of mortality 3,6 than studies that assigned weights to selected diseases. 10 Despite prolific use, the Charleson Comorbidity Index showed little or limited predictive power on trauma mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contents of the data file are reported elsewhere. 17 The CNS Registry System augments and validates the data through medical chart review and through interviewing a representative sample of patients. The Institutional Review Board of the Medical University of South Carolina approved this study.…”
Section: Data Sourcesmentioning
confidence: 99%